Congenital anonychia. - Milano, A. (European Journal of Pediatric Dermatology, 2008)
Anonychia is a rare condition (2) consisting in the lack of the nail lamina. It can affect some or all the nails of the hands and/or feet. Anonychia can be congenital or acquired. The congenital form, which can also affect the bone of the phalange due to the close anatomical and embryological relationship between the nail bed and the periosteum (3), can be isolated or part of the spectrum of complex inherited syndromes. The isolated form is usually inherited as an autosomal recessive trait. Recently congenital anonychia was associated to missense mutations and deletions (1) of RSPO3 gene codifying for the protein R-spondin 4 WNT β-catenin activating. This protein play a significant role in the development and regulation of the cell morphology, proliferation and motility (3).